Influence of Polyvinyl Pyrrolidone on Absorption and Radiation Transitions of Mn\(^{2 + }\) ions in Mn-doped ZnS Nanoparticles - Thai, Dang Van; Thang, Pham Van; Ben, Pham Van; Van, Bui Hong; Thi, Tran Minh; Nhat, Hoang Nam (Communications in Physics, 2016)
ZnS:Mn nanoparticles were synthesized by co-precipitation method from the precursors solutions of 0.1M Zn(CH\(_{3}\)COO)\(_{2}\), Na\(_{2}\)S and Mn(CH\(_{3}\)COO)\(_{2}\) then were capped with polyvinyl pyrrolidone. The XRD patterns showed that the ZnS:Mn nanoparticles possessed the \(T_d^2 - F4\bar {3}m\) cubic structure with the average crystallite size of several nanometers. At 300~K, the obtained photoluminescence spectra showed only a wide yellow-orange band centered at 603 nm, which should be attributed to the radiation transition of [\(^{4}\)T\(_{1}(^{4}\)G)\( \to ^{6}\)A\(_{1}(^{6}\)S)] of Mn\(^{2 + }\)(3d\(^{5})\) cations in the ZnS matrix. The excitation spectra recorded at 300 K on the other hand featured a strong photoluminescence band around 310-334 nm, which were assigned to the near band-edge absorption transition of ZnS host lattice, in addition with three weaker bands relating to the absorption transitions of [\(^{6}\)A\(_{1}(^{6}\)S) \( \to \) \(^{4}\)T\(_{2}(^{4}\)D)]: 430 nm, [\(^{6}\)A\(_{1}(^{6}\)S) \( \to \) \(^{4}\)A\(_{1}(^{4}\)G) -- \(^{4}\)E(\(^{4}\)G)]: 468 nm, and [\(^{6}\)A\(_{1}(^{6}\)S) \( \to  ^{4}\)T\(_{2}(^{4}\)G)]: 498 nm of Mn\(^{2 + }\)(3d\(^{5})\) cations. It was shown that the capping affected only the intensities of emissions bands.